A study of Yusof Ghani’s artworks : the ‘Wajah’ series paintings from 2006 to 2010 / Mozhgan Ramezani - Ramezani, Mozhgan (2015)
Among the artists in Malaysia, Yusof Ghani is one of the most established and prolific Abstract Expressionist painters in the Malaysian modern art scene. The Wajah series paintings (2006-2010) created by Yusof Ghani is his latest venture into the art world. According to Yusof Ghani there is not any well-written research about Wajah series and the reason might be that although Wajah series was exhibited in Indonesia (2010) and in Canada (2009), it has never been shown in Malaysia. Moreover, currently there are limited references and materials documenting Malaysian art. Thus, the researcher’s concern for the lack of research on Malaysian art for present and future generations led the researcher to embark on this issue as a research. This qualitative research aims to analyze the selected paintings of Wajah series to identify the characteristics of the art elements and principles, determine the technique and explain the main concept of these paintings. The researcher used maximal variation sampling strategy in which the researcher selected six paintings of Wajah series which are still available in Yusof Ghani’s art gallery called Tapak located in Shah Alam, Malaysia. The Narrative Design Method was used for conducting this research. The researcher collected the data through one-on-one interviews with the artist, field-notes, audio materials and documents. The collected data were analyzed using Art Appreciation Theory by Harry S. Broudy as the core theoretical framework in the phase of analyzing the samples. The results show that the eyeless faces in Wajah series do not represent any specific identity. Instead they are symbolic representation of humankind in general. Each piece of this series contains a different narrative and the expressive faces address social issues related to human attitudes. One of the most common features of all the selected paintings is the highly textured surfaces through the technique of impasto as well as modelling technique by sculpting the surface before the paint is applied. Controlled palette of a few hues with a limited tonal scale of dark and light and the ambiguous space of eyeless faces in these paintings set the right ambience for particular mood of these faces. It also can be concluded that Yusof Ghani’s works are technically influenced by the formalistic considerations of Abstract Expressionism in the USA. The relationship between paintings of Wajah series with Abstract Expressionism is clearly seen in the treatment of line and form, the spontaneous and expressive brushstrokes and the randomly placed paint by dripping and dribbles of paint onto the canvas. The Western Abstract Expressionist works are considered to be unconventional non-figurative images. However, Yusof Ghani’s gestural style alternates between abstract work and figurative images and it is not purely Abstract Expressionist as seen in the context of Western art. It could be suggested that Yusof Ghani always emphasizes not only on exploring formalistic issues but also incorporating subject matter and social critiques in his works.